The Relationship Between Text and Context in Hadith Studies: The Theory of Asbāb al-Wurūd and its Significance in Understanding Hadith - Nurohman, Aris; Mustaqim, Abdul; Muhammadi, Qasem (Taqaddumi: Journal of Quran and Hadith Studies, 2025)
Understanding ḥadīth requires more than a literal reading of the text; it must also take into account the historical, social, cultural, and linguistic contexts behind the Prophet Muhammad’s sayings. The theory of asbāb al-wurūd serves as a critical approach in ḥadīth studies, as it helps to uncover the underlying reasons or circumstances surrounding a particular prophetic statement. Through a qualitative library-based research method, this study explores the relationship between text and context in ḥadīth, and highlights the significance of asbāb al-wurūd in preventing misinterpretation and deepening the understanding of Islamic legal rulings. The findings reveal that asbāb al-wurūd not only clarifies the meaning of a ḥadīth more accurately but also provides a dynamic, inclusive, and contextually grounded interpretation aligned with the principles of maqāṣid al-sharī‘ah. Nevertheless, this approach faces certain limitations, particularly when the context is not explicitly recorded or relies on weak chains of narration. Therefore, methodological caution and a critical approach are essential in applying the asbāb al-wurūd theory in contemporary ḥadīth scholarship.